Comparative analysis of mitochondrial genomes of Broussonetia spp. (Moraceae) reveals heterogeneity in structure, synteny, intercellular gene transfer, and RNA editing - Lai, Chanjuan; Wang, Jie; Kan, Shenglong; Zhang, Shuo; Li, Pan; Reeve, Wayne Gerald; Wu, Zhiqiang; Zhang, Yonghua (Frontiers in Plant Science, 2022)
The genus Broussonetia (Moraceae) is comprised of three non-hybrid recognized species that all produce high quality fiber essential in the development of papermaking and barkcloth-making technology. In addition, these species also have medicinal value in several countries. Despite their important economical, medicinal, and ecological values, the complete mitogenome of Broussonetia has not been reported and investigated, which would greatly facilitate molecular phylogenetics, species identification and understanding evolutionary processes. Here, we assembled the first-reported three complete Broussonetia (B. papyrifera, B. kaempferi, and B. monoica) mitochondrial genomes (mitogenome) based on a hybrid strategy using Illumina and Oxford Nanopore Technology sequencing data, and performed comprehensive comparisons in terms of their structure, gene content, synteny, intercellular gene transfer, phylogeny, and RNA editing. Our results showed their huge heterogeneities among the three species. Interestingly, the mitogenomes of B. monoica and B. papyrifera consisted of a single circular structure, whereas the B. kaempferi mitogenome was unique and consisted of a double circular structure. Gene content was consistent except for a few transfer RNA (tRNA) genes. The Broussonetia spp. mitogenomes had high sequence conservation but B. monoica with B. kaempferi contained more synteny blocks and were more related, a finding that was well-supported in organellar phylogeny. Fragments that had been transferred between mitogenomes were detected at plastome hotspots that had integrated under potential mediation of tRNA genes. In addition, RNA editing sites showed great differences in abundance, type, location and efficiency among species and tissues. The availability of these complete gap-free mitogenomes of Broussonetia spp. will provide a valuable genetic resource for evolutionary research and understanding the communications between the two organelle genomes.